Analisis Pengukuran Kinerja Karyawan Menggunakan Metode Human Resource Scorecard Pada Yayasan Mentari Indonesia Jaya - Aisah, Mutia Nur; Hastasari, Ratih (CV Warnak Johanna Nusantara, 2025)
The Human Resource Scorecard is a measurement tool used to assess a measurement of human resource (HR) performance in improving the organization's overall performance. In this study, the weight/priority of key performance indicators (KPIs) was calculated using the Analytical Hierarchy Process (AHP), where the results of the measurement were divided into four perspectives, the Financial perspective for the first criterion was 0.079 and the second criterion was 0.082 meaning excellent performance, the Customer perspective for the first criterion was 0.053 which meant outstanding performance and for the second criterion of 0.110 it meant that improvements needed to be made, The perspective of Internal Business Process for the first criterion is 0.046 and for the second criterion of 0.054 means excellent performance, and the Learning and Growth perspective is for the first criterion of 0.051 and the second criterion of 0.053 means excellent performance, this helps in more objective and structured decision-making. This research can contribute to the development of human resource management at Yayasan Mentari Indonesia Jaya, as well as provide insight into the application of HR Scorecard in non-profit organization certification